Eu tenho trabalho, eu sou cidadão! : considerações acerca da compreensão de cidadania por auxiliares de enfermagem da Cidade de Fortaleza - Lima, Ítalo Emanuel Pinheiro de (2008)
This work the explicit understanding of citizenship by mid-level professionals (nurse) who work in hospitals of the city and Fortaleza. This is an empirical research, where, from the report that these professionals be for them citizenship, we sought an understanding of how that ideal is affected by changes in the world of work.